A Multiprotein Complex Regulates Interference-Sensitive Crossover Formation in Rice . Issue 1 (2nd July 2019) - Zhang, Jie; Wang, Chong; Higgins, James D.; Kim, Yu-Jin; Moon, Sunok; Jung, Ki-Hong; Qu, Shuying; Liang, Wanqi
Abstract : In rice, OsSHOC1 and OsPTD constitute an XPF-ERCC1-like complex and collaborate with OsMSH5, OsHEI10, and OsZIP4 to control class I meiotic crossover formation. Abstract: In most eukaryotes, a set of conserved proteins that are collectively termed ZMM proteins (named for molecular zipper 1 [ZIP1], ZIP2, ZIP3, and ZIP4, MutS homologue 4 [MSH4] and MSH5, meiotic recombination 3, and sporulation 16 [SPO16] in yeast [ Saccharomyces cerevisiae ]) are essential for the formation of the majority of meiotic crossovers (COs). Recent reports indicated that ZIP2 acts together with SPO16 and ZIP4 to control CO formation through recognizing and stabilizing early recombination intermediates in budding yeast. However, whether this mechanism is conserved in plants is not clear. Here, we characterized the functions of SHORTAGE OF CHIASMATA 1 (OsSHOC1; ZIP2 ortholog) and PARTING DANCERS (OsPTD; SPO16 ortholog) and their interactions with other ZMM proteins in rice ( Oryza sativa ). We demonstrated that disruption of OsSHOC1 caused a reduction of CO numbers to ∼83% of wild-type CO numbers, whereas synapsis and early meiotic recombination steps were not affected. Furthermore, OsSHOC1 interacts with OsPTD, which is responsible for the same set of CO formations as OsSHOC1. In addition, OsSHOC1 and OsPTD are required for the normal loading of other ZMM proteins, and conversely, the localizations of OsSHOC1 and OsPTD were also affected by the absence of OsZIP4 and human enhancer of invasion 10 in rice (OsHEI10). OsSHOC1 interacts with OsZIP4 and OsMSH5, and OsPTD interacts with OsHEI10. Furthermore, bimolecular fluorescence complementation and yeast-three hybrid assays demonstrated that OsSHOC1, OsPTD, OsHEI10, and OsZIP4 were able to form various combinations of heterotrimers. Moreover, statistical and genetic analysis indicated that OsSHOC1 and OsPTD are epistatic to OsHEI10 and OsZIP4 in meiotic CO formation. Taken together, we propose that OsSHOC1, OsPTD, OsHEI10, and OsZIP4 form multiple protein complexes that have conserved functions in promoting class I CO formation.